Selecting a translation equivalent: Factors to consider in the classroom - Alexandra Anisimova; Marina Pavlyuk; Serafima Kogotkova (Peoples' Friendship University of Russia (RUDN University), 2018)
The article focuses on the translation of terms in the Humanities, as well as the direct dependence of the translation equivalent on the mode of term coinage and its functioning. The authors argue that in the Humanities a lexical-semantic mode of term coinage is common, which makes the majority of terms consubstantial. This provision is developed in the article on the basis of Russian and English language materials. A number of contemporary English-Russian and Russian-English terminological dictionaries in various fields of the Humanities (politics, law, history) served as a data source for the research. The study relies on the methods of semantic analysis, dictionary definitions analysis, elements of system analysis and pragmatic analysis. The authors also describe the processes of terminologisation and determinologisation in the terminological systems of different fields of the Humanities and study various ways and methods of translation and equivalent screening.